La dimensione normativa dell'imprenditorialità accademica Tre casi di studio sugli investigatori principali, i loro gruppi di ricerca e i fattori di innesco dell'imprenditorialità accademica - nucciotti, alberto (Premio Tesi di Dottorato, 2017)
How does the current regulatory change in academic work influence the emergence of innovative commercial behaviours among industrial engineers within public universities? In particular, an attempt was made to reconstruct the emergence of an entrepreneurial regulatory dimension as a social construction process involving the main investigators and research groups in third academic mission activities. An in-depth qualitative analysis is carried out based on semi-structured interviews with academic engineering personnel, against the background of a reconstruction of both the development of industrial engineering as an academic discipline, and a recognition of the main changes that have taken place in the Italian academic field in recent years.